INVESTIGASI PERENCANAAN PEMBANGUNAN INFRASTRUKTUR: PERGESERAN PARADIGMA DAN PERTIMBANGAN PERENCANAAN MASA MENDATANG - Hansen, Seng (REKSABUMI, 2022)
Infrastructure planning is a challenging process especially for Indonesia which has limited investmentresources. Therefore, decision makers need to understand the planning process of infrastructuredevelopment. This study aims to investigate the infrastructure development planning process asimplemented by the three relevant ministries in Indonesia, and identify various aspects that shouldbe considered in the future infrastructure development planning process. Analysis of the interviewsfound that there has been a paradigm shift in infrastructure development planning in Indonesiaincluding governance, decision-making approach, administrative rules, financing sources, budgetingmindset, government role, planning approach, project preparation, and planning process model. Inaddition, this research has also succeeded in identifying various aspects of future infrastructureplanning considerations. Thus, this research is useful, especially for decision makers, by providing abetter understanding of infrastructure development planning practices in Indonesia.